Designing a Decision Support System for Prioritizing of Banks’ Branches - Ameneh Khadivar; Zahra Mohammadi (Journal of Information Technology Management, 2015)
The banks are the most important symbol of monetary market in any country without exception. As the optimum function of the banks have important role in economic development of the country, creating the ground for qualitative and quantitative promotion of the banks performance in healthy competition can play important role in achieving the goals. One of the methods helping the bank’s branches to identify the competitive position and performance quality is evaluation of their performance from various aspects and their ranking. The aim of present study is to design a decision support system based on Promethee II method as a complete and comprehensive method and by automatic ranking, despite considering the qualitative and quantitative indices, it is done in by low time and costs with high precision. Thus, it is possible to analyze the sensitivities to be sure of the initial selections and changing the indices and values dependent upon the environmental changes are provided for branches evaluators. The system output is the rank associated to each branch based on Promethee II method.